Occasional and Rare Lexemes in the Poetic Language of V. A. Zhukovsky (Methodology of Dictionary Interpretation) - D. N. Zhatkin (Научный диалог)
The article deals with the question of the lexicographic interpretation of the poetic language of V.A. Zhukovsky (1783—1852) in the form of the author’s dictionary, which became possible after the publication of the initial volumes of the “Complete Works and Letters” of the writer. Special attention is paid to poetic neologisms in the works of the first Russian romanticist. The question is raised about the typology of individual author’s lexemes. Occasionalisms properly, rare words and poetry, which became such as a result of the “replication” by many writers of successful and historically promising author’s neologisms of their predecessors are distinguished. The occasional units that are found in Zhukovsky’s translation of Homer’s poem “The Odyssey” and perform specific aesthetic functions are analyzed. The results of a comparative analysis of Zhukovsky’s poetic language with the lexicon of poets of the 18th — 20th centuries (N. M. Karamzin, I. I. Dmitriev, D. V. Davydov, K. N. Batyushkov, P. A. Vyazemsky, N. M. Yazykov , A. I. Polezhaev, D. V. Venevitinov, M. Yu. Lermontov and others) are presented in the article. The novelty of the research is seen in the fact that for the first time the neological layer of Zhukovsky’s poetic language is comprehended. The relevance of the study is due to the possibility of using the observations, facts and conclusions stated in it in the theory and practice of lexicography — when compiling explanatory, historical and author’s dictionaries.